Automatization of plasma density profile analysis by the multichannel microwave interferometer measurements for the Torsatron U-2M - Ocheretenko, V.L.; Berezhnyj, V.L.; Prokopenko, A.V.; Pinos, I.B. (Вопросы атомной науки и техники, 2008)
The paper presents the description of the density profile computing methods by the five-channel probing on the base of the developed program code and gives the results of model investigations. Описані методи розрахунку профілю густини при п'яти канальному зондуванні на підставі розробленого програмного коду і приведені результати модельних досліджень. Описаны методы расчета профиля плотности при пятиканальном зондировании на основании разработанного программного кода и приведены результаты модельных исследований.